If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(30 + s) = 4(s + 1a) (30 * 3 + s * 3) = 4(s + 1a) (90 + 3s) = 4(s + 1a) Reorder the terms: 90 + 3s = 4(1a + s) 90 + 3s = (1a * 4 + s * 4) 90 + 3s = (4a + 4s) Solving 90 + 3s = 4a + 4s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-4s' to each side of the equation. 90 + 3s + -4s = 4a + 4s + -4s Combine like terms: 3s + -4s = -1s 90 + -1s = 4a + 4s + -4s Combine like terms: 4s + -4s = 0 90 + -1s = 4a + 0 90 + -1s = 4a Add '-90' to each side of the equation. 90 + -90 + -1s = -90 + 4a Combine like terms: 90 + -90 = 0 0 + -1s = -90 + 4a -1s = -90 + 4a Divide each side by '-1'. s = 90 + -4a Simplifying s = 90 + -4a
| 2w+6=30 | | 2m+1=6m+2 | | 8(31.25+-0.5)+4y=250 | | x^4+6x^2+2x=0 | | 21m+36=3m | | 14x-21=49 | | (1/6x-5)-(6/5-6x) | | 8(x-9)=12 | | -3.4=.4j | | 49=25/1y | | 7c-7b=x | | 3(x+7)-4(x+3)=10 | | 12+50=949.88 | | 6y+(-4)= | | -2x=5x-9x+16-10 | | 7=.75*20+4 | | -3/4*8 | | 3+66x=33x+22 | | -x/4=-22 | | 4(7x+1)=312 | | .6h=1.8 | | 2(3y-6)= | | 8x+3y=101 | | -4(8+5x)=-32 | | 14=4a+2 | | 5x+11=7-2x | | -94=-2(5m+7) | | -2(7x-5)+3=-14x+13 | | p/7=6.8.k/4=2 | | 3x+11=12+8x | | 193=-x+96 | | -9x-13=50 |